Seizure, an Explosive Effect of a Lightning Strike: A Case Report (Global Journal of Medical Research, 2023)
Lightning strike injuries have a high morbidity rate because of critical alterations of the circulatory system respiratory system and central nervous system Most lightning-related deaths occur immediately after injury because of arrhythmia or respiratory failure We describe the case of a patient who experienced a seizure and respiratory distress secondary to a lightning strike and how we obtained a return of spontaneous circulation and intact neurological survival
Keywords: seizure; lightning; injury; (aeronautics); management; prevention